2020
DOI: 10.1103/physrevb.101.085402
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization-induced topological superconductivity in a Rashba nanowire

Abstract: We analyze the influence of dimerization on the topological phases of a Rashba nanowire proximitized to a superconducting substrate. We find that periodic alternations of the hopping integral and spin-orbit coupling can lead to band inversion, inducing a transition to the topologically nontrivial superconducting phase that hosts Majorana zero-energy modes. This "dimerization-induced topological superconductivity" completely repels the topological phase of the uniform nanowire, whenever they happen to overlap. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Then, value of h c depends on model parameters in nontrivial manner and can be determined analytically (more details can be found in Ref. [36]), but still, in the limit of δ → 0, condition (4) remains unchanged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, value of h c depends on model parameters in nontrivial manner and can be determined analytically (more details can be found in Ref. [36]), but still, in the limit of δ → 0, condition (4) remains unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…Similar analysis of the system can be performed in the momentum space (more details can be found in Ref. [36]). In this case, system can be studied via spin resolved spectral function A kσ (ω) = −1/π Im c kσ |c † kσ .…”
Section: Methodsmentioning
confidence: 99%
“…, is even in momentum k. Note that the intrasublattice odd-ω amplitudes F AA,BB are finite when eitherη or η is nonzero (t and are always assumed to be nonzero), and thus a consequence of the intrinsic sublattice symmetry breaking in the SC SSH model [63,64] but also predicted to appear in other systems such as in buckled quantum spin Hall insulators [55], or in nanowires with Rashba spin-orbit coupling [56]. For η =η = 0 the intrasublattice odd-ω amplitudes vanish.…”
Section: Bulk Pair Correlationsmentioning
confidence: 99%
“…For instance, it has been shown that in buckled quantum spin Hall insulators bulk odd-ω correlations appear due to a staggered order parameter but no sign of higher energy gaps in the DOS was reported [55]. Even more interestingly, it has recently been shown in nanowires with Rashba spin-orbit coupling that intrinsic staggered hopping and spin-orbit coupling can induce a topological superconducting phase that completely repels the topological phase of the uniform nanowire [56]. Since these nanowires represent one of the most investigated platforms for one-dimensional topological superconductivity [57][58][59], the reported staggered-induced topological phase is within experimental reach and its fundamental understanding is, therefore, important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation